How Dallas became frack free: hydrocarbon governance under neoliberalism. (December 2015) - Fry, Matthew; Brannstrom, Christian; Murphy, Trey
Local-scale government ordinances that attempt to delay or displace oil and gas drilling in their territories are common in regions with hydrocarbon extraction activities. Drawing on literature from policy mobilities and resource and energy governance, this paper analyzes policymaking processes that resulted in a December 2013 ordinance in Dallas, Texas, which established a 1500 foot (457.2 meter) setback between gas wells and residences, making drilling (with hydraulic fracturing) nearly impossible. Dallas was not the first city in the region to adopt an oil and gas drilling ordinance; indeed, many regulatory provisions were copied from other regional cities. This paper explains policy mobility in the Dallas policymaking process in terms of anti-political practices and hydrocarbon institutions that, overall, determine neoliberal hydrocarbon governance. City governments cede some of the political process to gas drilling task forces that work to render setbacks technical. Legal classification of subsurface hydrocarbons as the mineral estate creates a legal gray area that confounds municipal regulatory authority and gives discursive power to mineral owners to threaten municipal officials with lawsuits. Both of these anti-political strategies encouraged selective copying and morphing of other policy provisions by the Dallas city government. Adopting longer municipal setback distance regulations represents a type of contestation of neoliberalism situated between complete deregulation and overt opposition.